The Red Army Faction in prison: narratives of isolation and resistance 1970-1995 - Emmerich, Fabienne (2013)
The thesis is a qualitative study that analyses the personal narratives of isolation and resistance of former Baader-Meinhof prisoners (RAF) in the period 1970-1995 within the context of imprisonment and penality in Gennany. The thesis constructs a picture of isolation and resistance through these individual narratives that illustrate how a state policy to control the communication of individual RAF prisoners was translated into techniques of immobilization -solitary confinement- and surveillance -searches, censorship and monitoring-. The narratives recount how these techniques, though central to security and order in prison, were applied and adapted in order to disable the group both within prison and on the outside, and to diminish the (political) resolve of the individual prisoner. The narratives also give insight into individual and collective resistance to isolation, namely the rationales of individual survival and striving for community in the pursuit of collective detention of RAF prisoners. The thesis contributes to the literature on RAF imprisonment by framing the lived experiences of former women and men RAF prisoners and the meanings they attach to isolation and resistance within a power and gendered dimensions of prison life and penality. The study also hopes to contribute wider discussions on imprisonment and penality in Gennany, in particular the governance of women and men prisoners who are constructed as dangerous.